Estudio de factibilidad para la inversión de nueva maquinaria en el molino CONAGRO S.A.S (2022)
Molino CONAGRO SAS is a company that was established more than 10 years ago, and is dedicated to the production of milling products through laboratory processes, drying, shelling, polishing, grain selection and packaging, where the main brand is IMPERIAL rice (own brand).